Prevalence and Genetic Diversity of Cronobacter Species Isolated From Four Infant Formula Production Factories in China - Lu, Yan; Liu, Peng; Li, Changguo; Sha, Miao; Fang, Jingquan; Gao, Jingwen; Xu, Xiaoxi; Matthews, Karl R. (Frontiers in Microbiology, 2019)
ABSTRACT The aim of this study was to investigate the prevalence and genotypic characteristics of Cronobacter isolated from powdered infant formula (PIF) manufacturing facilities and identify the potential source of contamination. A total of 42 Cronobacter isolates (5%) were detected in 835 environmental samples collected during the surveillance study. These isolates included C. sakazakii (n=37), C. malonaticus (n=3) and C. turicensis (n=2). The isolates were divided into 14 sequence types (STs) by multi-locus sequence typing (MLST) and 21 pulsotypes (PTs) using pulsed-field gel electrophoresis (PFGE). The dominant C. sakazakii sequence types were ST3 (n=12) and ST21 (n=10), followed by ST136 (n=6). The major PTs were PT22 (n=12) and PT17 (n=4) based on 100% similarity. Strains isolated from samples collected at the same production facility showed closer phylogenetic relation than those collected from distinct facilities. The result of extensive traceback sampling showed that PIF residues (PIF dust in production areas), fluid bed, drying area, floor, and soil samples collected adjacent to production facilities were primary positive areas for Cronobacter. The present study outlines an effective approach to determine prevalence and genetic diversity of Cronobacter isolates associated with contamination of PIF.